PKM KEWIRAUSAHAAN PEMBUATAN KERIPIK PISANG LUMER COKLAT - Andi Tenri Ampa; Hikmayani Subur; Andi Caezar To Tadampali; Muhammad Ilyas Thamrin Tahir; Andi Annisa Sulolipu (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This community service aims to improve the skills and income of the community through the production of chocolate banana chips. This activity includes training for housewives and MSME actors on the technique of making banana chips with an attractive chocolate coating. In addition to providing knowledge about the production process which includes the selection of raw materials, processing, and proper packaging, this program also teaches aspects of product marketing effectively. It is estimated that through the innovation of the products produced, the community can utilize the potential of local bananas as raw materials and increase the competitiveness of their products in the market, thereby opening up new economic opportunities and improving welfare. In addition, this community service program also emphasizes the importance of aspects of cleanliness, food safety, and the use of simple technology in the production process. Training participants are given an understanding of how to process bananas into processed products with added value, while introducing various digital marketing techniques to expand market reach. Thus, the community not only masters technical skills in the production of chocolate banana chips, but is also able to manage businesses more professionally and sustainably. This program is expected to be a model of empowerment that can be applied in other communities, thereby encouraging local economic growth through innovative and competitive food products.